2022
DOI: 10.3390/app122312088
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Potentially Probiotic L. lactis Isolates from Polish Fermented Cow Milk for the Production of Cottage Cheese

Abstract: Lactococcus lactis bacteria are used as starter cultures in cottage cheese and fermented milk production due to their acidification and contribution in the creation of the characteristic sensory features. The aim of the research was to carry out isolation, genetic identification, and verification of the probiotic properties of selected Lactococcus lactis isolates obtained from Polish fermented cow milk and apply the best strains to produce cottage cheese with good rheological and sensory characteristics. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…These findings are comparable to those obtained with the probiotic Lactobacillus sp. strain in the earlier investigation [53,54].…”
Section: Discussionmentioning
confidence: 72%
“…These findings are comparable to those obtained with the probiotic Lactobacillus sp. strain in the earlier investigation [53,54].…”
Section: Discussionmentioning
confidence: 72%
“…However, the present study demonstrated that the percentage of co-aggregation of all isolates with Gram-positive pathogen (L. monocytogenes) was significantly higher than with Gramnegative pathogen (E. coli). Results of previous studies did not show a relationship between the percentage of co-aggregation and Gram stain of the pathogen (Nami et al, 2019;Pytka et al, 2022;Kanak et al, 2023;Yang et al, 2023). Research evidence has shown that the co-aggregation percentage is dependent only on incubation time, probiotics, and pathogen strain (Kanak et al, 2023).…”
Section: Isolatesmentioning
confidence: 80%
“…Moreover, none of the strains presented any activity of trypsin (the enzyme that can be related with pathogenicity of some microorganisms in human) or β-Glucuronidase related to transformation of pre-carcinogens into carcinogens and stimulation of colon cancer [ 66 , 67 ]. Activity of enzyme aminopeptidases like arylamidases and esterases may influence product properties because of their biotransformation ability [ 21 , 67 , 68 , 69 ]. Four strains also presented activity of N-acetyl-β-glucosaminidase, an enzyme with the primary functions of targeting and hydrolyzing oligosaccharides containing chitin [ 70 ] that may possibly arise in the biocontrol and biotransformation of some fungal- and invertebrate-based foods.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of yeasts and lactic acid bacteria often occurs in a synergistic manner, where they mutually enhance their growth and survival [ 16 , 17 , 18 ]. Examples of fermented products that can be sources for the isolation of probiotic strains are cheese, dough, dairy products, fermented fruits and vegetables, and traditional food and beverages [ 19 , 20 , 21 ]. Among such products, wines deserve attention as a source of probiotic microorganisms due to the richness of their microbiota [ 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%